Non-leptonic two-body decays of Λb0 in light-front quark model - C.Q. Geng (Physics Letters B, 2021)
We study the non-leptonic two-body weak decays of Λb0→pM with M=(π−,K−) and (ρ−,K⁎−) in the light-front quark model under the generalized factorization ansatz. By considering the Fermi statistic between quarks and determining spin-flavor structures in baryons, we calculate the branching ratios (Bs) and CP-violating rate asymmetries (ACPs) in the decays. Explicitly, we find that B(Λb0→pπ−,pK−)=(4.18±0.15±0.30,5.76±0.88±0.23)×10−6 and ACP(Λb0→pπ−,pK−)=(−3.60±0.14±0.14,6.36±0.21±0.18)% in comparison with the data of B(Λb0→pπ−,pK−)=(4.5±0.8,5.4±1.0)×10−6 and ACP(Λb0→pπ−,pK−)=(−2.5±2.9,−2.5±2.2)% given by the Particle Data Group, respectively. We also predict that B(Λb0→pρ−,pK⁎−)=(12.13±3.27±0.91,2.58±0.87±0.13)×10−6 and ACP(Λb0→pρ−,pK⁎−)=(−3.32±0.00±0.14,19.25±0.00±0.80)%, which could be observed by the experiments at LHCb.